2012
DOI: 10.1002/ar.22420
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐Mount Imaging Demonstrates Hypervascularity of the Pancreatic Ducts and Other Pancreatic Structures

Abstract: Confocal microscopy in combination with commercial software is frequently used to generate three-dimensional images of tissue architecture. Here we report a novel, whole-mount imaging protocol technique that allows detailed three-dimensional imaging of adult pancreatic structures. This technique provides an improved appreciation of the anatomical detail of pancreatic structures and of the relationship between the pancreatic ducts and islets. In addition, imaging of the pancreatic ducts revealed a previously un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This approach, especially in combination with whole-mount imaging, provides an excellent appreciation of pancreatic ductal anatomy and labeling efficiency in the mouse pancreas. 30,31 In conclusion, AAV6-mediated tissue tropism, combined with a sox9 shorter promoter and direct intraductal viral delivery can achieve durable and specific pancreatic duct tagging. This method, along with whole-mount imaging, should complement existing methods for the study of pancreatic duct lineages.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This approach, especially in combination with whole-mount imaging, provides an excellent appreciation of pancreatic ductal anatomy and labeling efficiency in the mouse pancreas. 30,31 In conclusion, AAV6-mediated tissue tropism, combined with a sox9 shorter promoter and direct intraductal viral delivery can achieve durable and specific pancreatic duct tagging. This method, along with whole-mount imaging, should complement existing methods for the study of pancreatic duct lineages.…”
Section: Discussionmentioning
confidence: 91%
“…28 Whole-Mount Staining and Immunohistochemistry Whole-mount immunofluorescence staining was carried out as described previously. [29][30][31] In brief, mice were infused with 10 ml PBS, followed by 10 ml 4% paraformaldehyde (PFA). The pancreatic tissues were then harvested and fixed in 4% PFA for 2 h in 4 1C.…”
Section: Generation and Purification Of Aav Serotype 6 Virusesmentioning
confidence: 99%
“…As in the fish, rodent CACs proliferate in response to pancreas injury (Gasslander et al, 1992; Hayashi et al, 1999; Hayashi et al, 2003). Several other studies have observed endocrine cells near to or embedded in the ductal tree during normal growth or regeneration (Bonner-Weir et al, 1993; El-Gohary et al, 2012; Gu and Sarvetnick, 1993; Li et al, 2010; Phillips et al, 2007; Rooman and Bouwens, 2004; Rosenberg, 1995; Weaver et al, 1985; Xu et al, 1999; Xu et al, 2008; Yoneda et al, 2013). Indeed, Ngn3-positive cells lining the ducts contribute to β cell expansion induced by overexpressing Pax4 in α cells (Al-Hasani et al, 2013).…”
Section: Centroacinar Cells As Adult Progenitorsmentioning
confidence: 94%
“…β-cell replication (1,2) and neogenesis (35) are the two main mechanisms that have been proposed for the formation of new β-cells. β-cell replication is generally accepted as the predominant mechanism for the generation of new β-cells in the adult islet (1), but it remains unclear how such a terminally differentiated cell can undergo proliferation (6).…”
Section: Introductionmentioning
confidence: 99%